Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.13181/mji.v22i1.518
|View full text |Cite
|
Sign up to set email alerts
|

HIV-related stigma and discrimination: a study of health care workers in Banda Aceh, Indonesia

Abstract: Latar belakang: Tujuan dari penelitian ini untuk mengetahui tingkat stigma dan diskriminasi tenaga kesehatan terhadap orang dengan HIV/AIDS (ODHA) serta menentukan faktor yang mempengaruhinya.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 19 publications
(39 reference statements)
3
30
1
1
Order By: Relevance
“…Previous studies also found conflicting findings. 11,26 In addition, previous studies found that HCPs who were working with high HIV case-load had lower stigmatized attitudes scores compared to HCPs with low HIV case-load. 1,30,31 This study found that stigmatized attitudes toward PLHIV among HCPs with low HIV case-load were very common.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Previous studies also found conflicting findings. 11,26 In addition, previous studies found that HCPs who were working with high HIV case-load had lower stigmatized attitudes scores compared to HCPs with low HIV case-load. 1,30,31 This study found that stigmatized attitudes toward PLHIV among HCPs with low HIV case-load were very common.…”
Section: Discussionmentioning
confidence: 96%
“…The items were selected from previous research. 11,26 To measure the stigmatized attitudes, the HCPs were asked to rate each item on a five-point Likert scale, indicating their agreement or disagreement (1 -Disagree strongly; 2 -Disagree somewhat; 3 -Neither agree nor disagree; 4 -Agree somewhat; and 5 -Strongly agree). The higher the score on this scale, the higher the level of stigmatized attitudes.…”
Section: Observed Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…It is a reflection of fear and the unknown, driven by ignorance and helplessness. As a consequence of stigma, or when stigma is acted upon, discrimination is said to occur, which is an unfair act or unjust treatment towards an individual or group based on identified characteristics [1,2].…”
Section: Introductionmentioning
confidence: 99%